2022
DOI: 10.1177/00110000221129606
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self-Compassion Among Adaptive and Maladaptive Perfectionists in University Students

Abstract: Using the tripartite model of perfectionism that accounts for combined characteristics of the Perfectionistic Strivings and Perfectionistic Concerns dimensions, this study explored the mediating role of self-compassion to explain differences between adaptive and maladaptive perfectionists in four psychological distress domains: depression, generalized anxiety, social anxiety, and academic distress. A sample of 3,112 university students were classified into adaptive, maladaptive, and nonperfectionists. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 64 publications
(108 reference statements)
2
12
0
Order By: Relevance
“…Findings reporting low levels of positive self-compassion components and high levels of negative self-compassion components in maladaptive perfectionists may be related to and explained by the irrational cognitions associated with the constant desire of being perfect and the intolerance towards flaws and imperfections ( Abdollahi et al, 2020 ; Ferrari et al, 2018 ). According to Kawamoto and his colleagues (2023) , individuals dealing with maladaptive perfectionism hold unattainable desires for flawlessness and exceptionally lofty standards that make them hypercritical about themselves. This conduct could be due to their inclination towards self-validation instead of internalizing self-compassion ( Tobin & Dunkley, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings reporting low levels of positive self-compassion components and high levels of negative self-compassion components in maladaptive perfectionists may be related to and explained by the irrational cognitions associated with the constant desire of being perfect and the intolerance towards flaws and imperfections ( Abdollahi et al, 2020 ; Ferrari et al, 2018 ). According to Kawamoto and his colleagues (2023) , individuals dealing with maladaptive perfectionism hold unattainable desires for flawlessness and exceptionally lofty standards that make them hypercritical about themselves. This conduct could be due to their inclination towards self-validation instead of internalizing self-compassion ( Tobin & Dunkley, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that adaptive perfectionists tend to report higher levels on positive self-compassion components than maladaptive perfectionists, because they are able to acknowledge their imperfections without harsh self-criticism and are more likely to practice self-care ( Stoeber & Damian, 2014 ; Stoeber & Otto, 2006 ). In addition, they demonstrate mindfulness and kindness towards themselves to manage the stress associated with striving for excellence ( Kawamoto et al, 2023 ). It seems that, by cultivating a sense of self-compassion and accepting one's own imperfections alongside striving for excellence, individuals can achieve higher levels of well-being while avoiding the negative effects often seen in non-adaptive forms of perfectionism, since the challenges are faced as an opportunity for growth and improvement ( Dunkley et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, mixed support has been garnered for the link between perfectionistic strivings and social anxiety. Some studies have found a positive relationship between perfectionistic strivings and social anxiety (Juster et al, 1996), while others have found a negative relationship (Kawamoto et al, 2023), or no relationship (Levinson et al, 2013; Nepon et al, 2011). Some researchers suggest that perfectionistic strivings is only linked to psychopathology if it occurs in the presence of perfectionistic concerns (Alden et al, 2002).…”
Section: Theoretical Application Of Perfectionism In Models Of Social...mentioning
confidence: 99%
“…Self-compassion can moderate or even nullify the harmful effects of negative attributions, which is undoubtedly the most exciting finding thus far. Kawamoto et al [82] found that self-compassion plays a significant role in dividing adaptive and maladaptive perfectionism; it has an adaptive function for perfectionists who inevitably need to accept their imperfections. According to Shin and Lim [7], self-kindness can affect individuals' mental health, as registered in our correlation analysis.…”
Section: Correlations and Regression Modelmentioning
confidence: 99%